Nutraceuticals and blood pressure control: a European Society of Hypertension position document. Issue 5 (May 2020) - Borghi, Claudio; Tsioufis, Konstantinos; Agabiti-Rosei, Enrico; Burnier, Michel; Cicero, Arrigo F.G.; Clement, Denis; Coca, Antonio; Desideri, Giovambattista; Grassi, Guido; Lovic, Dragan; Lurbe, Empar; Kahan, Thomas; et al.
Abstract : N/A: High-normal blood pressure (BP) is associated with an increased risk of cardiovascular disease, however the cost–benefit ratio of the use of antihypertensive treatment in these patients is not yet clear. Some dietary components and natural products seems to be able to significantly lower BP without significant side effects. The aim of this position document is to highlight which of these products have the most clinically significant antihypertensive action and wheter they could be suggested to patients with high-normal BP. Among foods, beetroot juice has the most covincing evidence of antihypertensive effect. Antioxidant-rich beverages (teas, coffee) could be considered. Among nutrients, magnesium, potassium and vitamin C supplements could improve BP. Among nonnutrient-nutraceuticals, soy isoflavones could be suggested in perimenopausal women, resveratrol in insulin-resistant patients, melatonin in study participants with night hypertension. In any case, the nutracutical approach has never to substitute the drug treatment, when needed.